2021
DOI: 10.12659/ajcr.932945
|View full text |Cite
|
Sign up to set email alerts
|

Giant Cell Arteritis as an Uncommon Cause of Chronic Cough: A Case Report

Abstract: Patient: Female, 27-year-old Final Diagnosis: Giant cell arteritis Symptoms: Cough Medication:— Clinical Procedure: — Specialty: Pulmonology Objective: Unknown etiology Background: Chronic cough is a common medical concern. Giant cell arteritis (GCA) is an uncommon cause of chronic cough and is not usually suspected since symptoms can be non-specific. We present a case of chronic cough due to GCA in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…A previous report has shown that 13% of patients with GCA may exhibit cough symptoms, primarily dry cough [ 6 ]. Several previous studies have reported GCA complicated by chronic bronchitis [ 7 ]. Chronic bronchitis can be prevalent among older patients; 13% of women and 18.6% of men in older populations have chronic bronchitis diagnosed based on clinical symptoms and computed tomography [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…A previous report has shown that 13% of patients with GCA may exhibit cough symptoms, primarily dry cough [ 6 ]. Several previous studies have reported GCA complicated by chronic bronchitis [ 7 ]. Chronic bronchitis can be prevalent among older patients; 13% of women and 18.6% of men in older populations have chronic bronchitis diagnosed based on clinical symptoms and computed tomography [ 8 ].…”
Section: Discussionmentioning
confidence: 99%